Caracterização do repertório acústico do botocinza, sotalia guianensis, e impacto de embarcações no nordeste do brasil - Martins, Dalila Teles Leão (2010)
The wide distribution along the Brazilian coast of specie Sotalia guianensis has been growing interest in searchers on the ecology of this species, addition to commercial interests by whalewatching. This work described the accoustic repertory of S. guianensis and their behavior associated and found if underwater noises affect this repertorie in Pipa-RN. It were analyzed 18:49h of recordings maked between april and june/2009. It were found 3258 whistles, 289 calls, 873 clicks and no gargle. The frequencies range of guiana dolphins was 1 a 48kHz and may be related to system response recorder and population s regionalization. The frequencies overlaps the noise made by motorboats, schooners and water bomb. The behavior travelling ocurred siletly in 72,58% and socialization presented no sound (56,4%) and presence of sound (43,6%). This great absence of sound may be relacioned to saving energy, probably because in this behaviors they can use physical and visual contacts. The foraging presented highest records of all class noise with 46,84% clicks, 33,84% whistles and 9,02% calls. All this sounds occurred differently in each behavior (travelling: x2 = 134,35 df = 3 p = 0,0001; foraging: x2 = 19,83 df = 3 p= 0,00018 and socialization x2 = 60,35 df = 3 p = 0,0001). It was possible to determine that underwater noise cause changes in the repertorie and does a considerable increase in whistle s number and reduce clicks. Also occurs changes in some whistles (FI: t=2,42, p=0,015; FF: t= -2,22, p=0,025), calls (FMI: t= -3,13, p=0,001; FMA: t= -3,49, p=0,0005; FD: t= -2,21, p=0,027; D: t=2,89, p=0,004) and clicks parameters (D: t= -3,85, p=0,0001; I: t= -5,32, p=0,0001) during presence of noise. These changes may be a strategy of these animals to win this sound barrier. We can not say which noise has more impact, ix however the water bomb seems to affect more the clicks and the motorboats seems to affect the others sounds. Little is know about auditive sensibility of this specie, but daily exposure to this noise may cause damage and this specie appears to have residence. The specie conservation is necessary because the population already seems to suffer damage as decrease in length of stay, number of individuals entering the inlet and the apparent diminution in the foragind during vessels presence and control standards and ambiental education can help. So, we can advance in knowledge about the ecology of this specie especially when it come to bioacoustics and their behaviors associated and reveals some of the impacts that the noise have brought to this population